Setting priorities to address cardiovascular diseases through universal health coverage in low- and middle-income countries. Issue 1 (22nd February 2017) - Watkins, David A; Nugent, Rachel A
Abstract : Over the past decade, universal health coverage (UHC) has emerged as a major policy goal for many low- and middle-income country governments. Yet, despite the high burden of cardiovascular diseases (CVD), relatively little is known about how to address CVD through UHC. This review covers three major topics. First, we define UHC and provide some context for its importance, and then we illustrate its relevance to CVD prevention and treatment. Second, we discuss how countries might select high-priority CVD interventions for a UHC health benefits package drawing on economic evaluation methods. Third, we explore some implementation challenges and identify research gaps that, if addressed, could improve the inclusion of CVD into UHC.